Proceedings of the Twenty-Sixth International Joint Conference on Artificial Intelligence 2017
DOI: 10.24963/ijcai.2017/31
|View full text |Cite
|
Sign up to set email alerts
|

Object Allocation via Swaps along a Social Network

Abstract: This article deals with the allocation of objects where each agent receives a single item. Starting from an initial endowment, the agents can be better off by exchanging their objects. However, not all trades are likely because some participants are unable to communicate. By considering that the agents are embedded in a social network, we propose to study the possible allocations emerging from a sequence of simple swaps between pairs of neighbors in the network. This model raises natural questions regarding (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 7 publications
4
65
0
Order By: Relevance
“…[14] analyses optimality in the setting where pairs of agents exchange items or services. The influence of neighbourhood structures in terms of item exchange and its influence on convergence to stable and optimal allocations is studied in [20,13]. Exchange dynamics with restricted preferences orderings are considered in [40,17].…”
Section: Allocation Of Indivisible Goodsmentioning
confidence: 99%
“…[14] analyses optimality in the setting where pairs of agents exchange items or services. The influence of neighbourhood structures in terms of item exchange and its influence on convergence to stable and optimal allocations is studied in [20,13]. Exchange dynamics with restricted preferences orderings are considered in [40,17].…”
Section: Allocation Of Indivisible Goodsmentioning
confidence: 99%
“…Damamme et al (2015) firstly proved that the problem is NP-hard even to decide whether any one of a subset of objects is reachable for each agent. Gourvès, Lesca, and Wilczynski (2017) further showed that OBJECT REACHABILITY is polynomially solvable under star-structures and NP-complete under tree-structures. For the network being a path, they solved the special case where the given agent is an endpoint (a leaf) in the path and left it unsolved for the general case.…”
Section: Introductionmentioning
confidence: 99%
“…A swap between two agents is allowed when they are mutually beneficial from the exchange. This natural rule for HOUSING MARKET has been studied in the literature (Damamme et al 2015;Gourvès, Lesca, and Wilczynski 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent papers combine graphs and fair division of indivisible items by assuming that agents are located in the vertices of a graph. For instance, Chevaleyre et al (2007) and Gourvès et al (2017) consider the case where each agent has an initial endowment of goods and can trade with her neighbors in the graph. The authors study outcomes that can be achieved by a sequence of mutually beneficial deals.…”
Section: Introductionmentioning
confidence: 99%